Effect of Coverage on Adsorptions of CO on Ni(110) Surface. (22nd July 2021) - Yan, Sun
Abstract : The adsorptions of CO on Ni(110) surface at different coverages have been investigated by first-principle calculations. The results show that CO will be bonded at short bridge site preferentially. And CO preferentially absorbs upright at short bridge sites and top sites at 1/6 monolayer coverage. With increasing coverage to 0.5 ML, the enhanced steric repulsion leads to the slope of CO. For 1/6 and 1/2 monolayer coverage, CO is mainly bonded at short bridge site and atop site simultaneously at a certain ratio. When CO coverage is 1 monolayer, CO absorbs at short bridge site and forms p2mg configuration. As the coverage of CO is increased to finally form the p2mg structure, there is a continuous frequency shift up to the value 1962.27 cm -1 . The vibration frequencies we calculated are consistent with relative experimental results. DOS of CO molecules and Ni atoms are discussed too.